The efficiency of northeastern isolates of Green muscardine fungi metarhizium spp. on controlling economic insect pests (Thai) - Natongkham, Anchalee; Sirimungkararat, Sivilai; Saksirirat, Weerasak; Urairong, Hathairat; Kaewrat, Benjamat (Asia-Pacific Journal of Science and Technology, 2017)
Green muscardine fungus, Metarhizium sp. is one of the most important entomopathogenic fungi. It is able to infect diverse insects worldwide. Therefore, this study was undertaken with 16 randomized isolates of Metarhizium spp., collected from the northeast of Thailand. Of these, the quantitative chitinase activity and effectiveness on control of the major insect pests were carried out. The adults of Culex mosquito (Culex quinquefasciatus) (vector of elephantiasis or filariasis) and larvae of beet armyworm (Spodoptera exigua) (Agricultural key insect pest) were the representative test insects. During the infection process of the fungus, there were various produced enzymes. Chitinase is one of the enzymes, which plays an important role in infection process. Hence, the quantitative chitinase activity was investigated. It was found that average chitinase activities were among 6.88-127.75 GlcNAc-µmol/mg protein/hr. The three highest chitinase activities were isolates IPKKU222, IPKKU184 and IPKKU241 with values of 127.75, 70.61 and 57.39 GlcNAc-µmol/mg protein/hr, in descending order. Chitinase activity of isolate IPKKU222 was significantly different (P<0.05) with other isolates. In addition, the ability on infection of insect pests under laboratory conditions at 28±2°C, 75-83 % RH was tested. The results showed that the adult of Culex mosquito had average mortality percentages of 6.00-80.67 by using spore concentration of 6x108 spore/ml. Of these, the most ef-fective isolate was IPKKU234 (80.67%) followed by IPKKU178 (70.67%) and IPKKU230 (66.00%). The infection rate of IPKKU234 was significantly different (P<0.05) with IPKKU178 and IPKKU230. On beet armyworm using spore concentration of 1x108 spore/ml., the average infection was 3.33-40.00%. The highest infection was IPKKU249 (40.00%) followed by isolates IPKKU234 (36.67%) and IPKKU178 (33.33%), which were not significantly different (P>0.05).